2019
DOI: 10.1002/phar.2246
|View full text |Cite
|
Sign up to set email alerts
|

Integrase Inhibitors: After 10 Years of Experience, Is the Best Yet to Come?

Abstract: The era of the integrase strand transfer inhibitors (INSTIs) for the treatment of human immunodeficiency virus (HIV) infection began with raltegravir in 2007. Since that time, several other INSTIs have been introduced including elvitegravir, dolutegravir, and, most recently, bictegravir, that have shown great utility as part of antiretroviral regimens in both treatment-naive and treatment-experienced patients. At present, antiretroviral guidelines fully endorse the INSTI class as part of all first-line treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 99 publications
(128 reference statements)
0
46
0
Order By: Relevance
“…Both clinical trials and real-life data have demonstrated the high efficacy, favorable safety profile, tolerability, low toxicity, and relatively high genetic barrier to resistance of INSTIs for both naïve and ART-experienced patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical trials and real-life data have demonstrated the high efficacy, favorable safety profile, tolerability, low toxicity, and relatively high genetic barrier to resistance of INSTIs for both naïve and ART-experienced patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Another INSTI, cabotegravir (CAB), is the newest drug that is being developed as a long-acting injectable for monthly or quarterly administration and as an oral tablet for daily use for the treatment and prevention of HIV-1 infection, and it is currently in the late phase of clinical trials [8,15]. At present, a long-acting regimen with CAB has been approved by Health Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Two classes of inhibitors have been developed to inhibit IN functions. INSTIs, such as raltegravir or dolutegravir, inhibit the strand-transfer step catalyzed by IN and are used in antiviral therapies [ 18 ]. ALLINIs induce abnormal IN multimerization, prevent interaction on IN with viral RNA, generating eccentric non-infectious particles defective in viral replication [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary function of integrase is integration of viral DNA into the host genome. Integrase strand-transfer inhibitors (INSTIs) that target this function have been developed and are used to treat HIV-1 infections [ 18 ]. Recent studies showed that IN is also essential during morphogenesis of the particles [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This function has been successfully targeted by a class of antiretrovirals known as integrase strand-transfer inhibitors (INSTIs) [ 3 ]. Four FDA-approved INSTIs, raltegravir [ 4 ], elvitegravir [ 5 ], dolutegravir [ 6 ], and bictegravir [ 7 ], have become key components of anti-retroviral therapy regimens and are both highly effective and well tolerated ([ 8 , 9 , 10 ], reviewed in [ 11 ]). A fifth, cabotegravir [ 12 ], is currently in late stage clinical trials.…”
Section: Introductionmentioning
confidence: 99%